Social Capital Impact on Social Religious Influence in the Quran Teachings - Saeid Moidfar; Muhammad Bagher Akhondi (آموزه‌های قرآنی, 2013)
The aim of this paper is to examine religious social influence through the enhancement of social capital in the Quran teachings. This achieves through the qualitative content analysis of the Quran interpretations, coding and conceptual classification. The research findings show that the enhancement to the message, arousing emotions and enthusiasm, friendly ties; social warm, friendly and face to face relationship, reliability and responsibility make religious social influence develop. Consequently, the enhancement of social capital in the society can increase social influence and leads to change the attitude and beliefs.